Remarkable magnetostructural coupling around the magnetic transition in CeCo0.85Fe0.15Si - Correa, V.F.; Betancourth, D.; Sereni, J.G.; Caroca-Canales, N.; Geibel, C.; Sereni, Julián; Correa, Víctor Félix (IOP Publishing, 2016)
Fil: Correa, V.F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina